ANALISIS PERTUMBUHAN Spirulina sp. DENGAN KOMBINASI PUPUK YANG BERBEDA - nilam cahya; Saptono Waspodo; Bagus Dwi Hari Setyono (Jurnal Perikanan Unram, 2020)
This study aims to providing a combination of fertilizer (urea, NPK dan TSP) withdifferent doses on the growth of Spirulina sp. This research was conducted in October 2019which took place in a private graham cendana Blok J no 4, Sekarbela, Mataram City. This studyuses a completely randomized design with four treatment namely treatment A: (0 g/l Urea; 0 g/lNPK; 0 g/l TSP) (kontrol), B: (0,2 g/l Urea; 0, 01g/l NPK; 0,004 g/l TSP), C: (0,3 g/l Urea; 0,02g/l NPK; 0,006 g/l TSP), D: (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP).The results of the studyfor 9 days of culture process in treatment D with a combination of fertilizer (urea, NPK dan TSP)as much (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP) the highes density results obtained as muchas 831 ind/ml while the lowest value obtained in treatment A (without fertilizer) is as much 505ind/ml and the highest daily growth rate is obtained in treatment D with a combination offertilizer (urea, NPK dan TSP) (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP) this is as much as0.413 ind/ml/day while the lowest value obtained in treatment A (without fertilizer) is 0.484ind/ml/day.